CONTROL OF EXECUTIVE POWER DELEGATED AUTHORITIES IMPLEMENTATION BY LOCAL GOVERNMENTS - Kuzmenko S.L. (Pressing Problems of Public Administration, 2018)
The procedure for monitoring the acts of local self-government bodies regarding the exercise of delegated powers of executive authorities is considered.